Association between cardiovascular diseases and COVID-19 pneumonia outcome in Indonesia: a multi-center cohort study - Burhan, Erlina; Mubarak, Farhan; Adilah, Siti Aliyah Said Utriyani; Sari, Cut Yulia Indah; Ismail, Efriadi; Astuti, Puji; Hanifah, Yasmina; Wiyarta, Elvan; Suryana, Nana Maya (Frontiers in Medicine, 2023)
Background: COVID-19 is a pandemic affecting 185 countries, including Indonesia. Cardiovascular diseases (CVD) in COVID-19 patients were linked to worse clinical outcomes. However, the association remained inconclusive due to limited data in Indonesia. This study aimed to determine the association between CVD in COVID-19 pneumonia patients with its clinical outcomes. Methods: This retrospective cohort study was conducted in four Indonesian hospitals, enrolling 584 adult COVID-19 pneumonia patients from September 2020 to July 2021. Patients were categorized into two groups: non-CVD and CVD (hypertension, coronary artery disease (CAD), chronic heart failure (CHF), hypertensive heart disease (HHD), arrhythmia, cardiomegaly, left ventricular hypertrophy (LVH), mitral regurgitation (MR), and myocardial injury (MI)). Clinical outcomes include in-hospital mortality, intensive care unit admission, ventilator use, earlier death, and prolonged hospital stay. Mann-Whitney test was used for analysis. Results: The most common CVD was hypertension (48.1%), followed by MI (10.6%), CAD (9.2%), CHF (6.8%), HHD (3.1%), arrhythmia (1.7%), and others (0.7%). The in-hospital mortality rate was 24%, and patients were hospitalized for a median of 12 days. MI was the only CVD that increased in-hospital mortality (RR 2.105). It was also significantly increased in patients with diabetes mellitus (RR 1.475) and chronic kidney disease (RR 2.079). Meanwhile, prolonged hospital stay was associated with any CVD (RR 1.553), hypertension (RR 1.511), MI (RR 1.969), CHF (RR 1.595), diabetes mellitus (RR 1.359), and cerebrovascular disease (RR 2.203). Conclusion: COVID-19 pneumonia in patients with CVD, specifically MI and hypertension, worsens the COVID-19 clinical outcomes.